Performance Audit of National Rural Health Mission (NRHM) in Nagaland (2009-2014) - CAG of India (CAG of India)
National Rural Health Mission (NRHM) was launched in April 2005 by the Government of India (GoI) in all the States to bring about significant improvements in health system and health status of the people, especially those in rural areas. The Mission seeks to provide universal access to equitable, affordable and quality health care which is accountable and responsive to the needs of the people. The performance audit covering various activities of National Rural Health Mission (NRHM) and National Health Mission (NHM) in Nagaland for the period 2009-10 to 2013-14 was carried out by the CAG of India, by test check of records in four districts out of 11 selected by applying Simple Random Sample Without Replacement. Eight Community Health Centers (CHCs) out of nine, 12 Primary Health Centers (PHCs) out of 53 and 20 Sub-Centers (SCs) out of 175 in the four sampled districts were selected using Probability Proportional to Size Without Replacement. In addition to this, four District Hospitals (DH) in the four sampled districts were also covered. This performance audit revealed the following: The inadequate conduct of various surveys to assess the requirements of healthcare facilities in the rural areas led to partial assessment of the quality of prevailing healthcare services in the State. The financial management was not streamlined and there were instances of financial commitments not being honoured and delays in release of funds which impacted the achievement of Mission objectives. It was noticed that there were various deficiencies in construction activities and purchase of quality medicines and equipment. The targets set in respect of various healthcare programmes were not achieved. Monitoring of the implementation of the mission activities was not carried out as envisaged in the Mission guidelines. This resulted in inadequate translation of the Mission’s objectives to tangible benefits in the State.
For the period 2009-10 to 2013-14
Keywords: Nagaland